Revisiting global patterns of frontal sinus aplasia utilizing computed tomography. (October 2020) - Butaric, Lauren N.; Jones, Griffin C.; Garvin, Heather M.
Highlights: The XR-method consistently provided higher aplasia rates compared to the CT-method. Females present higher aplasia rates versus males, regardless of method. Arctic/Oceanians present the highest, and Euro/Africans the lowest, rates of aplasia. Reference data must use same methodology and samples to support identifications. Standardized methods need to be established to ensure comparability and accuracy. Abstract: While frontal sinus aplasia (agenesis, absence) has been proposed as a potential marker in forensic positive identifications, frequency rates are likely dependent upon how presence is defined. This study investigates how two methods of defining frontal sinus presence affects aplasia frequency rates. Using CT scans of 772 adult individuals from diverse geographic regions, frontal sinus presence was assessed two ways: 1) the XR-method— coded present if the sinus extended above the supra-orbital line, and 2) the CT-method— coded present with any indication of the frontal sinus. The XR-method consistently provided higher aplasia frequencies, averaging an 18.31% discrepancy with the CT-method. Method discrepancies were higher in females (averaged-sides: 24.6%) than males (averaged-sides: 13.82%). Oceanian individuals displayed the highest aplasia rates using either method, and the highest discrepancy between methods (averaged-sides: 31.30%); Europeans, displaying the lowest aplasia rates in either method, also displayed the lowest method discrepancy (average-sides: 7.37%). Fisher's Exact tests on the biologically-defined CT aplasia rates indicate females are significantly different from males for unilateral aplasia (p = 0.0035); Arctic populations are significantly different from most groups (all p < 0.005), exception being Oceanian. Results suggest the lower, biologically-defined CT aplasia rates are more useful in corroborating identifications than the inflated XR frequencies and illustrate the importance of citing aplasia rates from similarly-composed samples. However, due to practicality and resource availability, the XR-method may be more appropriate. Most importantly, reported aplasia rates from one method should be cited in casework utilizing the other method.